Neutral atmosphere temperature trends and variability at 90 km, 70°N, 19°E, 2003-2014 - Holmen, Silje Eriksen; Hall, Chris; Tsutsumi, Masaki (Atmospheric Chemistry and Physics, 2016)
Source: doi:10.5194/acp-16-7853-2016 Neutral temperatures at 90 km height above Tromsø, Norway, have been determined using ambipolar diffusion coefficients calculated from meteor echo fading times using the Nippon/Norway Tromsø Meteor Radar (NTMR). Daily temperature averages have been calculated from November 2003 to October 2014 and calibrated against temperature measurements from the Microwave Limb Sounder (MLS) on board Aura. Large-scale periodic oscillations ranging from ∼ 9 days to a year were found in the data using Lomb–Scargle periodogram analysis, and these components were used to seasonally detrend the daily temperature values before assessing trends. Harmonic oscillations found are associated with the large-scale circulation in the middle atmosphere together with planetary and gravity wave activity. The overall temperature change from 2003 to 2014 is −2.2 K ± 1.0 K decade−1, while in summer (May–June–July) and winter (November–December–January) the change is −0.3 K ± 3.1 K decade−1 and −11.6 K ± 4.1 K decade−1, respectively. The temperature record is at this point too short for incorporating a response to solar variability in the trend. How well suited a meteor radar is for estimating neutral temperatures at 90 km using meteor trail echoes is discussed, and physical explanations behind a cooling trend are proposed.